Application of cryopreserved umbilical cord blood and placenta-derived products in the treatment of infertility in a patient with diminished ovarian reserve. Case report - Feskova, Anna; Feskov, Oleksandr; Konoplia, Lina; Zhylkova, Yevhenia; Feskova, Iryna; Blazhko, Olena (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):241